Language to contest legitimacy: The acceptability of Qanun Putroe Phang in light of the Acehnese discourse - Yunisrina Qismullah Yusuf; Teuku Muttaqin Mansur; Kismullah Abdul Muthalib (Peoples' Friendship University of Russia (RUDN University), 2024)
This research aims to describe the perspectives of the Acehnese people on Qanun Putroe Phang. The theoretical approach employed is legal linguistics, utilising Critical Discourse Analysis. The focus of the research is on public opinion regarding the qanun, which is a regional regulation governing government administration and community life in Aceh, Indonesia. This qanun is known for prioritising the protection of women and children in Aceh since the reign of Sultan Iskandar Muda (from 1607 until 1636). The study involved interviews with 50 informants aged 20-80 years old, with 10 informants from each of the following districts: Aceh Besar, Pidie, North Aceh, South Aceh, and West Aceh. The interviews explored the participants' perceptions of Qanun Putroe Phang and their understanding of its role in protecting the rights of women and children within Acehnese society. The results indicated that 84% of respondents believe the qanun is, and will continue to be, relevant even in contemporary life. However, 16% of respondents viewed the qanun as a burden for families, particularly those with many daughters or economic difficulties. Many respondents suggested that the qanun should be revised to encourage its implementation in a manner that is not mandatory but persuasive for the Acehnese people.